1998
DOI: 10.1007/s004060050025
|View full text |Cite
|
Sign up to set email alerts
|

Interinformant reliability of family history information on psychiatric disorders in relatives

Abstract: Knowledge on the reliability of family history information is essential for every family study. However, systematic analyses of interinformant reliability of family history information on individual relatives have not yet been published. Consequently, family history information on 1306 first-degree relatives and spouses of patients and of control subjects was collected from at least two other family members using questionnaires. Interinformant reliability was acceptable for dementia [Kappa = 0.58, 95% confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 27 publications
2
19
1
1
Order By: Relevance
“…Gershon and Guroff (1984) have indicated that the values for diagnostic agreement between a clinician's diagnosis of unipolar depression in an individual and a relative's report is 0.42, which is considered fair. Structured interviews such as the one we used can optimize the acquisition of family history information (Heun and Muller, 1998;Ptok et al, 2001). Nevertheless, the lack of direct interview data from the relatives of the subjects represents a significant limitation in a population-based study.…”
Section: Discussionmentioning
confidence: 99%
“…Gershon and Guroff (1984) have indicated that the values for diagnostic agreement between a clinician's diagnosis of unipolar depression in an individual and a relative's report is 0.42, which is considered fair. Structured interviews such as the one we used can optimize the acquisition of family history information (Heun and Muller, 1998;Ptok et al, 2001). Nevertheless, the lack of direct interview data from the relatives of the subjects represents a significant limitation in a population-based study.…”
Section: Discussionmentioning
confidence: 99%
“…History of psychiatric illness was not included in FABS secondary to its subjectiveness and low interinformant reliability. 17,18 We also excluded lowdensity lipoprotein and A1C because the results most likely would not be available in the emergency setting.…”
Section: Construct An Intuitive Scoring Systemmentioning
confidence: 99%
“…However, this was not feasible within the framework of the present study. As shown by other studies confronted with this difficulty [12,15], the diagnosis of disorders occurring in the family therefore has to be made with the greatest possible care as far as incorrect/correct is concerned.…”
Section: Gas Scorementioning
confidence: 99%